(untitled) (Biological Sciences - PJSIR, 2007)
. Th e q LJ a nti ty of oi l i n l oca l var i eti es of sweet n nd b i t te r apr i cot w a fou n d to be m ore th an t h at ear l i er report ed for t h e I n dian vari eti es. D ot h , sweet an d bi tt er a pr i cot oi l s, w ere semi -d ry i n g type . Refract i ve i n dex of bi tt er apri cot oi l wa s h i gher whereas, free fatty acids were more i n sweet apric ot oi l. A m oun t of cyan i de, cad mi um , an t i mon y, a r sen i c, l ead a n d copper as we l l as of pa l mi t i c ac i d i n si gn i fi c.in t l y i n creased wi t h ri pen i n g, be i n g m ore i n b i t t er apri cot oi l. M aj or d ifferen ce w as n ot ed i n fatty aci d com posi t i on . L i nol e i c acid w a s p r esent i n h i gh er a m ou n t i n sweet apri cot oi l (2 1 .4%) th an i n bi tter apri cot oi l ( 19 . 6’Yo) .Concentrati on of pa l m i t i c a c i d i n sweet oi l w as 5.0%, w h i l e i n bi tt er o i l , i t was 6.4%.